2007
DOI: 10.1007/s00464-007-9285-x
|View full text |Cite
|
Sign up to set email alerts
|

Marginal ulceration after laparoscopic gastric bypass: an analysis of predisposing factors in 260 patients

Abstract: Helicobacter pylori may potentiate marginal ulcer formation. The authors hypothesize that H. pylori damages the mucosal barrier in a way that persists postoperatively, which may precipitate marginal ulceration even when the organism has been medically eradicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
126
2
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(143 citation statements)
references
References 37 publications
4
126
2
8
Order By: Relevance
“…A comparison of patients with and without marginal ulcers within 10 months after surgery demonstrated that marginal ulceration was more common among patients who tested positive for H. pylori even when adequately treated. 12 Other studies looking at complications following gastric bypass surgery in patients with H. pylori infection also suggest some relation between postoperative complications and the presence of H. pylori. 9,13 Although this may imply a benefit to preoperative screening and treatment, there are also conflicting studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of patients with and without marginal ulcers within 10 months after surgery demonstrated that marginal ulceration was more common among patients who tested positive for H. pylori even when adequately treated. 12 Other studies looking at complications following gastric bypass surgery in patients with H. pylori infection also suggest some relation between postoperative complications and the presence of H. pylori. 9,13 Although this may imply a benefit to preoperative screening and treatment, there are also conflicting studies.…”
Section: Discussionmentioning
confidence: 99%
“…9,12 Knowing the potential changes that this may cause, it is possible that histological consequences from H. pylori may be related to certain complications after bariatric surgery. A comparison of patients with and without marginal ulcers within 10 months after surgery demonstrated that marginal ulceration was more common among patients who tested positive for H. pylori even when adequately treated.…”
Section: Discussionmentioning
confidence: 99%
“…This induces exacerbation of the ulcer, even if the organism has already been treated. 63,68,69 All these factors may have influenced the increased prescription of antisecretory drugs observed in this study.…”
Section: Gastric Antisecretory Agentsmentioning
confidence: 90%
“…Development of stomach ulcers is one of the biggest and most common complications associated with the gastric bypass technique, 63,64 and it is reported in 1% to 20% of the patients after surgery. 65,66 Stomach ulcers may develop over the short term, possibly associated with technical problems at the intervention site.…”
Section: Gastric Antisecretory Agentsmentioning
confidence: 99%
“…Marginal entero-enteric ulcers are a well-documented complication of Roux-en-Y gastric bypass, with an incidence between 0.6% and 16% [4,5]. The majority of the published reports regarding post-gastric bypass marginal ulceration are retrospective; therefore, only symptomatic patients have been investigated, and the data we found from such studies are limited.…”
Section: Discussionmentioning
confidence: 99%